Pengaruh Realisasi Angaran Kesehatan, Anggaran Pendidikan dan Pariwisata Terhadap Penanggulan Kemiskinan di Provinsi Jawa Barat - Edward Zubir; Darwin Hartono; anton robiansyah; Selly Anastassia Amellia Kharis (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study was to analyze the effect of the realization of the health budget, the realization of the education and tourism budget on poverty in West Java in 2007-2021. This type of research is associative research with a quantitative approach. The analytical method used is multiple regression analysis. The results showed a constant value of -110.441, meaning that if the independent variables were the realization of the health budget, the realization of the education and tourism budget remained unchanged, assuming ceteris patribus then poverty would decrease by 110.441 units. Realization of the health budget has a negative and significant effect on poverty with a coefficient of 1.946. Realization of the education budget has a negative and significant effect on poverty with a coefficient of 1.548. Tourism has a negative and significant effect on poverty with a coefficient of 1.304. The Adjusted R Square result is 0.843 or 84.3 percent, thus the realization of the health budget variable, the realization of the education and tourism budget is able to determine the poverty variable by 84.3 percent. The results of the F test show that the calculated F is -17.150 greater than the F table value with df (0.05;3;11) of 3.587 with a probability value of 0.002. Thus, the realization of the health budget, the realization of the education and tourism budgets have a significant negative effect on poverty together.